(untitled) (Pixel :Jurnal Ilmiah Komputer Grafis, 2025)
The rapid development of information technology has encouraged organizations to implement computerized systems to improve document management efficiency and security. At PT Petrokimia Gresik, import document archiving was previously conducted using Google Drive and physical storage, which caused issues such as limited access control, risk of data loss, and slow document retrieval during audits. This study aims to design and develop a web-based Import Document Archiving Information System using the waterfall development method. The system was built using HTML, CSS, JavaScript, PHP, and MySQL. The results indicate that the system improves archiving efficiency, enhances data security, accelerates document search, and supports structured monitoring and validation processes.